Between cosmopolitan and classical: Persian in early colonial India, c.1757-1857 - Shah, Z (2017)
This thesis investigates the significance of Persian learning in Britain and India during the period of colonial expansion under the East India Company, from 1757 to 1857. It seeks to situate Persian in its wider social context in north India, and understand the significance and function of the language during a period which is typically described in terms of the decline of the Persianate world. It does so by studying Persian literary production and language-learning by a range of actors at different sites in north India. By examining the presence of Persianate texts and individuals in spaces and endeavours which are typically classified as modern (orientalist textual production in the colony, the rise of linguistic studies, colonial education and nineteenth-century Indian printing), this thesis emphasizes the ways in which Persianate relationships and sensibilities shaped these sites of Indian modernity, and were themselves altered in the process. This thesis shows that the reasons for the continued usage of Persian in late eighteenth and early nineteenth-century India went beyond its symbolic value as a marker of earlier Mughal power. Persian played an important role in shaping and constructing cosmopolitan literary and scholarly identities, as well as enabling spatial and social mobility. In so doing, this thesis hopes to contribute to the historiography of the Persianate world, as well as the histories of language, printing and education in colonial South Asia more broadly. In making these arguments, this thesis suggests a reappraisal of the ways in which the relationship between Indian modernity and cosmopolitan cultures now seen as 'classical' - such as that of Persian - is conceived. Rather than viewing Persian as a mere symbol of Mughal rule, a socially-grounded understanding of the Indian and colonial engagement with Persian is suggested. Understanding Persian in its social context in India, and recognizing the variety of spaces, languages and groups it interacted with challenges any neat categorization of the language as 'classical' or 'foreign' to India, or in opposition to vernacular or indigenous languages.